2018
DOI: 10.1101/484857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-induced phospho-ubiquitin formation causes parkin degradation

Abstract: Mutations in the E3 ubiquitin ligase parkin are the most common known cause of autosomal recessive parkinsonism. Multiple types of stress decrease parkin protein levels, an effect that may be relevant to sporadic Parkinson's disease (PD), but the mechanism(s) involved in this loss remain largely unclear. We sought to elucidate these mechanisms using a PD-relevant stressor, L-DOPA, the precursor to dopamine, which forms reactive oxygen species (ROS) as well as toxic quinones via auto-oxidation. We find that L-D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Parkin is a ubiquitin E3 ligase with a special role in the molecular mechanism of general neurodegeneration. 106 Mutations in the parkin gene have been implicated in autosomal recessive juvenile parkinsonism, an early onset and common familial form of PD. 107 RanBP2 localizes in the cytoplasmic filament of the nuclear pore complex and belongs to the SUMO E3 ligase family.…”
Section: Parkinmentioning
confidence: 99%
“…Parkin is a ubiquitin E3 ligase with a special role in the molecular mechanism of general neurodegeneration. 106 Mutations in the parkin gene have been implicated in autosomal recessive juvenile parkinsonism, an early onset and common familial form of PD. 107 RanBP2 localizes in the cytoplasmic filament of the nuclear pore complex and belongs to the SUMO E3 ligase family.…”
Section: Parkinmentioning
confidence: 99%
“…Recently, Kovalchuke and colleagues have demonstrated that other more physiological oxidative stressors like L-DOPA, lead to Parkin degradation. Although the exact mechanism of how Parkin is degraded following L-DOPA remains unclear, they show that PINK1 and phospho-Ub are involved in this pathway [175], demonstrating a similar mechanism to other mitochondrial stressors such as CCCP (mitochondrial uncoupler) [156]. This study suggests that oxidative stress or phospho-Ub may contribute to the loss of Parkin in PD.…”
Section: Pink1/parkin Pathwaymentioning
confidence: 57%